Bias Gender Dalam Berkomunikasi Ditinjau Dari Perspektif Bimbingan Dan Konseling - Ivana Qinthara; Arinnisa Nurzaman; Nazwa Nisa; Arby Julyhantoro; Siti Hamidah (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2023)
Communication is a necessity for every individual. Communication between men and women can form a gender identity. Especially in Indonesia with a patriarchal culture, gender is still deeply rooted in society. This gender creates various differences between men and women, one of which is in communication. In order not to form gender stereotypes, these communication differences need to be understood by each individual, both men, and women. The difference in communication between men and women also needs to be understood by counselors so that the counseling process can run effectively. Therefore, we try to explore how gender bias in communication is viewed from the perspective of guidance and counseling. This research was conducted using a descriptive design with a qualitative approach. Data was collected through a systematic literature study, a questionnaire method conducted via an online form to the general public, as well as semi-structured interviews with students and guidance and counseling teachers at the UPI Pilot Laboratory High School. The results of data analysis show that the ability to communicate in men and women tends to be proficient, both in the private and public spheres. Most of them are also considered capable and open in communicating both with the same sex and with the opposite sex. Efforts made by guidance and counseling counselors/teachers to be able to improve student's communication skills, namely through classical guidance services and individual services.